2024
DOI: 10.3389/fmed.2024.1285067
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of hematological indicators via explainable artificial intelligence in the diagnosis of acute heart failure: a retrospective study

Rustem Yilmaz,
Fatma Hilal Yagin,
Cemil Colak
et al.

Abstract: IntroductionAcute heart failure (AHF) is a serious medical problem that necessitates hospitalization and often results in death. Patients hospitalized in the emergency department (ED) should therefore receive an immediate diagnosis and treatment. Unfortunately, there is not yet a fast and accurate laboratory test for identifying AHF. The purpose of this research is to apply the principles of explainable artificial intelligence (XAI) to the analysis of hematological indicators for the diagnosis of AHF.MethodsIn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 72 publications
(72 reference statements)
0
1
0
Order By: Relevance
“…author found that unit increase of AST, ALT or CRP increases the odds of HF against CIHD for3.43%, 2.46% and 4.11% respectively, p-value < 0.05. Rustem Yilmaz et al [14] this research aims to utilize the concepts of explainable artificial intelligence (XAI) in analysing haematological indicators to diagnose Acute Heart Failure (AHF). XGBoost was used in conjunction with LASSO to diagnose AHF, the resulting model had an AUC of 87.9%, an F1 score of 87.4%, a Brier score of 0.036, and an F1 score of 87.4%.…”
Section: Literature Surveymentioning
confidence: 99%
“…author found that unit increase of AST, ALT or CRP increases the odds of HF against CIHD for3.43%, 2.46% and 4.11% respectively, p-value < 0.05. Rustem Yilmaz et al [14] this research aims to utilize the concepts of explainable artificial intelligence (XAI) in analysing haematological indicators to diagnose Acute Heart Failure (AHF). XGBoost was used in conjunction with LASSO to diagnose AHF, the resulting model had an AUC of 87.9%, an F1 score of 87.4%, a Brier score of 0.036, and an F1 score of 87.4%.…”
Section: Literature Surveymentioning
confidence: 99%